Estimation of the role of radiation in the plasma of electric arc discharge between Cu-C composites - Veklich, A.; Fesenko, S.; Murmantsev, A.; Boretskij, V. (Вопросы атомной науки и техники, 2021)
This work is devoted to investigation of the radiation in the plasma of electric arc discharge between Cu-C composite electrodes and estimation of its contribution during the determination of electron density from the energy balance equation (Elenbaas-Heller). The contribution of radiation energy in heat transfer is estimated as well. The calculation is carried out based on the preliminary experimentally obtained radial distribution of plasma temperature. For the correct solution of the energy balance equation, a Gaussian approximation of the plasma temperature profile is used. Estimation of the total current was used as a criterion for the need to take into account the radiation in the diagnostics of electric arc plasma.